The Destination Life Cycle Concept in Developing a Tourist Brand. Case of Mangystau of Kazakhstan - MARALBAYEVA, Sholpan M.; NIKIFOROVA, Nina V.; SMYKOVA, Madina R. (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021DO - 10.14505//jemt.v12.6(54).05, 2021)
The article aims to find the relation of positioning of a tourist destination to the life cycle of a territory (TALC). The research methodology is based on the marketing studies conducted as a survey of experts who works with tourists in Mangystau area of Kazakhstan. On the basis of the studies a model of the tourist brand’s positioning was developed in accordance with the territory’s stage of development, mainly for those visitors who seek for new places, since the area’s nature has almost “wild” and unexplored places and many historical and cultural objects which are located precisely in the unmanned and impassable steppe. The area’s brand structure was elaborated in accordance with the McKinsey model to build an appropriate positioning of the destination due to a stage of its life cycle. The finding of this study suggested that the strategy of the Mangystau tourist brand should be based on its identification, attributes and its life cycle’s stages and be aimed at positioning related to nature and cultural traditions that identified as the most valuable tourist attractions. The research applied the psychographic personality classification system to propose the type of tourists for whom that territory will be especially attractive.